Pyruvate dehydrogenase kinase regulates vascular inflammation in atherosclerosis and increases cardiovascular risk - Forteza, MJ; Berg, M; Edsfeldt, A; Sun, J; Baumgartner, R; Kareinen, I; Casagrande, FB; Hedin, U; Zhang, S; Vuckovic, I; Dzeja, PP; Polyzos, KA; et al. (Oxford University Press, 2023)
Aims Recent studies have revealed a close connection between cellular metabolism and the chronic inflammatory process of atherosclerosis. While the link between systemic metabolism and atherosclerosis is well established, the implications of altered metabolism in the artery wall are less understood. Pyruvate dehydrogenase kinase (PDK)-dependent inhibition of pyruvate dehydrogenase (PDH) has been identified as a major metabolic step regulating inflammation. Whether the PDK/PDH axis plays a role in vascular inflammation and atherosclerotic cardiovascular disease remains unclear.